THE EFFECT OF PRESERVICE TEACHERS' INFORMATION AND COMMUNICATION TECHNOLOGIES COMPETENCIES ON ACADEMIC SELF-EFFICACY AND ACADEMIC ACHIEVEMENT - Hüseyin Hüsnü Bahar; Recep ÖZ; Murat Tolga Kayalar (Novìtnâ Osvìta, 2023)
The purpose of this study was to measure the ICT competency levels and academic self-efficacy perception levels of preservice teachers and to determine if those levels were a significant predictor of their academic self-efficacy. For this purpose, the data were obtained from 411 volunteer students studying in the second, third, and fourth grades of the Teacher Training Undergraduate Programs at Erzincan Binali Yıldırım University Education Faculty. In total, 133 male and 278 female students participated in the study. As data collection tools, the Personal Information Form, the Information and Communication Technology Competencies Scale for Pre-service Teachers (ICTC-PT) developed by Tondeur et al. (2017) and adapted to Turkish language and culture by Alkan and Sarıkaya (2018) as well as the Academic Self-Efficacy Scale (ASES) developed by Kandemir (2010) were used. The Personal Information Form included information regarding department, grade, gender, and GPA. The reliability analyses of the scales were carried out, as well as multiple and stepwise regression analyses and descriptive statistics to address the research questions. As a result, it was determined that pre-service teachers' perception of ICT self-efficacy was at a high level. A moderate level of perception was observed in the sub-dimensions of ASE-CAP, ASE-AE, and ASE-APL among the participants. ICT-ID was found to be a significant predictor of ASE-CAP, but not of CSP-ICT. Although CSP-ICT was more closely related to general competencies, ICT-ID appeared to be more closely related to the skills required by the teaching profession. Based on the results of the study, the ASE-CAP, ASE-APL, and ICT sub-dimension scores were not significant predictors of GPA, whereas the ASE-AE score was a significant and positive predictor of GPA. It could be concluded from these findings that experiences and activities aimed at improving students' self-efficacy perceptions contributed positively to academic achievement in teacher training programs.